DEVELOPING WORD BUBBLE GAME TO TEACH VOCABULARY FOR ELEMENTARY SCHOOL IN THE ACADEMIC YEAR 2017/2018 - Abdullah Farih; Wahyu Maulidah (Reforma : Jurnal Pendidikan dan Pembelajaran, 2018)
The research aims at developing vocabulary materials based on Word Bubble Games for the students of Elementary School students’. The main purpose of this study is to help the English teachers to create fun activities in teaching English by introducing traditional Word Bubble games to the students. To reach the purpose of the study, the researcher employed Research and Development method (R&D) and adapted ADDIE’ model. The researcher used three instruments to obtain the data such as interview, questionnaires and observation. The obtained data will be classified based on the instrument used. To show the results, the researcher explained them in quantitative and qualitative approach. The results show that most of fifth grade students of MI Fathul Huda give a good response toward the developed games. In addition, the experts gave an excellent judgment to the developed materials. After finishing all the stages, the researcher finally provided prototype product. The prototype product is a handbook for the teachers to teach vocabulary. The book entitled “Gladhi English” which comprises of six lessons and ten games which have been modified in order to be applicable in teaching vocabulary. Key words: Word Bubble Games, Teaching Vocabulary